Qualitative and quantitative study of fetal posterior fossa during the first trimester in a Chinese population - Li Feng; Lijuan Sun; Jingjing Wang; Congxin Sun; Lijuan Lu; Zhikun Zhang; Yu Hu; Qingqing Wu (BMC Pregnancy and Childbirth, 2022)
Abstract Background To establish the normal reference ranges for parameters related to the fetal posterior fossa in the first trimester (11 ~ 13+6 weeks of gestation) and to analyze the relationship between them and crown-rump length (CRL) among the Chinese population. Methods Singleton pregnancies of 11 ~ 13+6 weeks (CRL:45 ~ 84 mm) with both parents from China were randomly selected from January 2021 to November 2021. The related parameters of the posterior fossa including cisterna magna (CM), intracranial translucency (IT), brain stem (BS), brain stem to the occipital bone (BSOB), and brain stem/brain stem to occipital bone (BS/BSOB) were evaluated and measured in nuchal translucency (NT) mid-sagittal section clearly by an experienced sonographer (operator 1). To assess the reproducibility of the measurements, we randomly selected 50 pregnant women. According to the blind method, operators 1 and 2 respectively screened and measured relevant parameters. In addition, operator 1 examined and measured relevant parameters again 2 h after the first. Results This study included 1663 fetuses. All fetuses can clearly show the three spaces of the fetal posterior fossa. The ICCs (95% CI) of intra-operator reproducibility of CM, IT, BS, BSOB, BS/BSOB were 0.981 (0.952 ~ 0.991, P < 0.001), 0.929 (0.866 ~ 0.961, P < 0.001), 0.970 (0.946 ~ 0.983, P < 0.001), 0.991 (0.974 ~ 0.996, P < 0.001), 0.939 (0.892 ~ 0.965, P < 0.001), respectively; The ICCs (95% CI) of inter-operator reproducibility 0.926 (0.860 ~ 0.960, P < 0.001), 0.810 (-0.083 ~ 0.940, P < 0.001), 0.820 (0.645 ~ 0.904, P < 0.001), 0.804 (0.656 ~ 0.888, P < 0.001), 0.772 (0.599 ~ 0.871, P < 0.001), respectively. There was a linear correlation between CRL and the parameters related to the posterior fossa (CM, IT, BS, BSOB, BS/BSOB). CM (mm) = -1.698 + 0.532 × CRL (cm) (r = 0.829, P < 0.001); IT (mm) = 0.701 + 0.179 × CRL (cm) (r = 0.548, P < 0.001); BS (mm) = 0.403 + 0.349 × CRL (cm) (r = 0.716, P < 0.001); BSOB (mm) = -0.277 + 0.719 × CRL (cm) (r = 0.829, P < 0.001); BS/BSOB = 0.747—0.021 × CRL (cm) (r = 0.196, P < 0.001). Conclusions Qualitative and quantitative assessment of the fetal posterior fossa structure was feasible in the first trimester. We constructed the normal reference ranges of CM, IT, BS, BSOB, and BS/BSOB. Furthermore, CM, IT, BS, and BSOB were positively correlated with CRL, but BS/BSOB was negatively correlated with CRL.